Production of Starch Films Using Propolis Nanoparticles as Novel Bioplasticizer - Villalobos, Karolina (2017)
Because starch is a biodegradable polymer with low cost and wide availability it is an attractive material for producing edible films for fruits. Films produced with pure starch have the disadvantage of being fragile. To overcome this issue, propolis nanoparticles were used as a novel plasticizer. Mechanical, thermal and morphological properties of the films containing 0.5, 1 and 3 wt.% propolis nanoparticles were evaluated. The best performance was obtained using 0.5 wt.% propolis, increasing the Young’s modulus and decreasing the glass transition temperature (Tg), showing their plasticizing effect. The results of scanning electron microscopy (SEM) and atomic force microscopy (AFM) images showed a homogenous material with a low quantity of cracks and higher roughness than the pristine starch film. A more hydrophobic material was obtained due to the resin and wax compounds present in the propolis nanoparticles. This study shows the novel use of propolis as plasticizer for starch films.